Youth and the Rural Economy in Africa Hard Work and Hazard - Sumberg, James (CABI, 2021)
This book unites recent findings from quantitative and qualitative research from across Africa to illuminate how young men and women engage with the rural economy and imagine their futures, and how development policies and interventions can find traction with these realities. Its 10 chapters are organized around commonly-made foundational claims: that large numbers of young people are leaving rural areas, have no interest in agriculture, cannot access land, can be the engine of rural transformation, are stuck in permanent waithood, and that the rural economy can provide a wealth of opportunity.